Proyecto de inversión para la exportación del producto agrícola no tradicional malanga hacia el mercado español - Pacheco Varas, Luis (2009)
This project presents a new alternative investment in the export of nontraditional agricultural product called Malanga, to the Spanish market. For that evaluates primary and secondary competitors, international prices, through marketing, target market analysis, plant design and production capacity. Ecuadorian land use, crop characteristics, collection and processing system after export. Although domestic demand is scarce, however exploits comprehensive feeding programs in Spain for the export of taro as a food of high nutritional content. And taking Spain as a target market, we have sought alternative marketing and sales operations through a Business Broker to tying our product wholesale markets in major Spanish cities, preferring locations where migrants are known to reside in Latin America, these who crave the latest product and will be the way to reach Spanish consumers (families).